Antifungal Potential of Synthetic Peptides against Cryptococcus neoformans: Mechanism of Action Studies Reveal Synthetic Peptides Induce Membrane–Pore Formation, DNA Degradation, and Apoptosis - Tawanny K. B. Aguiar; Nilton A. S. Neto; Cleverson D. T. Freitas; Ayrles F. B. Silva; Leandro P. Bezerra; Ellen A. Malveira; Levi A. C. Branco; Felipe P. Mesquita; Gustavo H. Goldman; Luciana M. R. Alencar; Jose T. A. Oliveira; Ralph Santos-Oliveira; et al. (Pharmaceutics, 2022)
Cryptococcus neoformans is a human-pathogenic yeast responsible for pneumonia and meningitis, mainly in patients immunocompromised. Infections caused by C. neoformans are a global health concern. Synthetic antimicrobial peptides (SAMPs) have emerged as alternative molecules to cope with fungal infections, including C. neoformans. Here, eight SAMPs were tested regarding their antifungal potential against C. neoformans and had their mechanisms of action elucidated by fluorescence and scanning electron microscopies. Five SAMPs showed an inhibitory effect (MIC50) on C. neoformans growth at low concentrations. Fluorescence microscope (FM) revealed that SAMPs induced 6-kDa pores in the C. neoformans membrane. Inhibitory assays in the presence of ergosterol revealed that some peptides lost their activity, suggesting interaction with it. Furthermore, FM analysis revealed that SAMPs induced caspase 3/7-mediated apoptosis and DNA degradation in C. neoformans cells. Scanning Electron Microscopy (SEM) analysis revealed that peptides induced many morphological alterations such as cell membrane, wall damage, and loss of internal content on C. neoformans cells. Our results strongly suggest synthetic peptides are potential alternative molecules to control C. neoformans growth and treat the cryptococcal infection.